2017
DOI: 10.1016/j.jsams.2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and sedentary time in relation to academic achievement in children

Abstract: ObjectivesTo investigate the independent and combined associations of objectively measured moderate-to-vigorous physical activity (MVPA) and sedentary time (ST) with reading and arithmetic skills.DesignCross-sectional/prospective.MethodsParticipants were 89 boys and 69 girls aged 6–8 years. MVPA and ST were measured using a combined heart rate and movement sensor and body fat percentage by dual-energy X-ray absorptiometry in Grade 1. Reading fluency, reading comprehension, and arithmetic skills were assessed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
61
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 33 publications
2
61
0
9
Order By: Relevance
“…Several systematic reviews are available on the effects of physical activity (Donnelly 2016; Fedewa 2011; Sibley 2003, Vazou 2016; Verburgh 2014), dietary (Ells 2008) and general school health interventions (Langford 2014; Murray 2007) on school achievement and cognitive outcomes in the general population. Although these systematic reviews may include some children with obesity or overweight, they lack a separate analysis of the effect estimates in our population groups of interest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several systematic reviews are available on the effects of physical activity (Donnelly 2016; Fedewa 2011; Sibley 2003, Vazou 2016; Verburgh 2014), dietary (Ells 2008) and general school health interventions (Langford 2014; Murray 2007) on school achievement and cognitive outcomes in the general population. Although these systematic reviews may include some children with obesity or overweight, they lack a separate analysis of the effect estimates in our population groups of interest.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a meta-analysis of 44 experimental and cross-sectional studies (in participants aged four to 18 years) indicates that increased physical activity caused significant overall improvement in cognitive function and school performance (Hedge's g = 0.32; standard deviation (SD) 0.27) (Sibley 2003). A recent meta-analysis of 21 experimental and quasi-experimental studies in children aged four to 16 years (N = 4044) also reported a moderate positive effect of physical activity interventions on cognitive outcomes (Hedge's g = 0.46, 95% confidence interval 0.28 to 0.64) (Vazou 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Core knowledge in teaching, is the knowledge of the competency of teachers to implement the learning process. Teachers should have an element of: (1) the content of knowledge; (2) a basic knowledge of pedagogy; (3) pedagogical content knowledge; (4) knowledge and curriculum; (5) knowledge in the context of learning; (6) knowledge and characteristics of learners; and (7) knowledge in effective learning objectives, exciting, and motivating learners to participate in activities PJOK.…”
Section: Discussionmentioning
confidence: 99%
“…(3) pedagogical content knowledge; (4) knowledge and curriculum; (5) knowledge in the context of learning; (6) knowledge and characteristics of learners; and (7) knowledge in effective learning objectives, exciting, and motivating learners to participate in activities PJOK.…”
Section: Introductionmentioning
confidence: 99%
“…During a typical school day, students have 3 distinct forms of participating in physical activity: (1) physical education, (2) recess, and (3) other unstructured physical activities (Slater et al, 2012). However, the recommended 150 mins/wk of physical activity is rarely met (Haapala et al, 2017).…”
Section: Introductionmentioning
confidence: 99%